PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN LINGKUNGAN PADA MATERI HUKUM HOOKE - Wewengkang, Pingkan Seila; Makahinda, Tineke; Sompotan, Armstrong; Londa, Treesje Katrina; Tumangkeng, Jeane Verra; Tiwow, Vistarani Arini (Charm Sains: Jurnal Pendidikan Fisika, 2025)
This study aims to determine the application of the Problem Based Learning (PBL) model with an environmental approach to Hooke's law material in improving learning outcomes. The study was conducted at SMA Negeri 1 Tondano using a quantitative method with a pretest-posttest control group design. The sample in this study were students of class XI 1 as the experimental class and XI 2 as the control class. Sampling used a simple random sampling technique. This study used a test instrument (pretest-posttest) consisting of 15 multiple-choice test items. The results showed that there were differences in learning outcomes between the experimental class that applied the problem-based learning model with an environmental approach and the control class. The average posttest results for the experimental class were 87.03 and the control class was 40.43. Based on the N-gain score obtained in the experimental class of 0.85, it is in the high category. Thus, it can be stated that the application of the problem-based learning model with an environmental approach to Hooke's law material can improve student learning outcomes.